European guidelines (S1) on the use of high-dose intravenous immunoglobulin in dermatology - Enk, Alexander; Hadaschik, Eva (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Background and objectives Treatment of severe dermatological autoimmune diseases and toxic epidermal necrolysis (TEN) with high-dose intravenous immunoglobulin (IVIg) is a well-established procedure in dermatology. As treatment with IVIg is usually considered for rare clinical entities or severe cases, the use of immunoglobulin is not generally based on data from randomized controlled trials usually required for evidence-based medicine. Since the indications for the use of IVIg are rare, it is unlikely that such studies will be available in the foreseeable future. Because first-line use is limited by the high costs of IVIg, the first clinical guidelines on the use of IVIg in dermatological conditions were established in 2008 and renewed in 2011. Methods The European guidelines presented here were prepared by a panel of experts nominated by the EDF and EADV. The guidelines were developed to update the indications for treatment currently considered effective and to summarize the evidence for the use of IVIg in dermatological autoimmune diseases and TEN. Results and conclusion The current guidelines represent consensual expert opinions and definitions on the use of IVIg reflecting current published evidence and are intended to serve as a decision-making tool for the use of IVIg in dermatological diseases.
First published: 30 December 2016
Gesehen am 08.11.2018